Molecular epidemiology of Staphylococcus aureus strains isolated from inpatients with infected diabetic foot ulcers in an Algerian University Hospital. (23rd March 2013) - Djahmi, N.; Messad, N.; Nedjai, S.; Moussaoui, A.; Mazouz, D.; Richard, J.–L.; Sotto, A.; Lavigne, J.–P.; Lina, G.
Abstract Staphylococcus aureus is the most common pathogen cultured from diabetic foot infection (DFI). The consequence of its spread to soft tissue and bony structures is a major causal factor for lower‐limb amputation. The objective of the study was to explore ecological data and epidemiological characteristics of S. aureus strains isolated from DFI in an Algerian hospital setting. Patients were included if they were admitted for DFI in the Department of Diabetology at the Annaba University Hospital from April 2011 to March 2012. Ulcers were classified according to the Infectious Diseases Society of America/International Working Group on the Diabetic Foot classification system. All S. aureus isolates were analysed. Using oligonucleotide arrays, S. aureus resistance and virulence genes were determined and each isolate was affiliated to a clonal complex. Among the 128 patients, 277 strains were isolated from 183 samples (1.51 isolate per sample). Aerobic Gram‐negative bacilli were the most common isolated organisms (54.9% of all isolates). The study of ecological data highlighted the extremely high rate of multidrug‐resistant organisms (MDROs) (58.5% of all isolates). The situation was especially striking for S. aureus [(85.9% were methicillin‐resistant S. aureus (MRSA)], Klebsiella pneumonia (83.8%) and Escherichia coli (60%). Among the S. aureus isolates, 82.2% of MRSA belonged to ST239, one of the most worldwide disseminated clones. Ten strains (13.7%) belonged to the European clone PVL+ ST80. ermA, aacA‐aphD, aphA, tetM, fosB, sek, seq, lukDE, fnbB, cap8 and agr group 1 genes were significantly associated with MRSA strains (p <0.01). The study shows for the first time the alarming prevalence of MDROs in DFI in Algeria.